(untitled) (#Tear: Revista de Educação, Ciência e Tecnologia, 2015)
Resumo: O presente artigo apresenta os resultados preliminares de um estudo realizado com licenciandos de Matemática de uma instituição pública de Boa Vista/RR relacionando interdisciplinaridade, situações-problema e questões ambientais locais e globais. Entre as premissas que motivaram os pesquisadores para a realização desses estudos estão: a urgência da questão ambiental na Região Amazônica da qual faz parte Roraima e a relevância de incluir os saberes matemáticos na compreensão desses aspectos por parte de docentes e discentes. Um grupo de 30 graduandos do primeiro semestre participou de atividades envolvendo a exposição dialogada, debates com docentes/pesquisadores e a aplicação de questionários compondo um conjunto de dados analisados por meio dos Métodos Mistos. A maior parcela dos estudantes considerou satisfatória a abordagem vivenciada na educação básica em relação à interdisciplinaridade (84%), situações-problema (63%) e questões ambientais (60%), embora considerem de grande relevância abordar esses aspectos na Licenciatura em Matemática, indicando boas possibilidades para a adoção de práticas educativas calcada na transversalidade e na interdisciplinaridade no âmbito da formação inicial de professores. Palavras-chave: Interdisciplinaridade. Educação Matemática. Formação de Professores. Educação Ambiental. Situações-problema. ENVIRONMENTAL EDUCATION IN THE INITIAL TRAINING OF TEACHERS OF MATHEMATICS OF BOA VISTA/RR: TRANSVERSAL THEMES AND INTERDISCIPLINARITY Abstract: This article presents the preliminary results of a study performed with licensees of Mathematics of a public institution of Boa Vista/RR correlating interdisciplinarity, problem situations, and local and global environmental issues. The assumptions that motivated the study are the urgency of the environmental issue in the Amazon region, the relevance of including the mathematical knowledges in understanding of these aspects on the part of teachers and students. A group of 30 undergraduate students of first semester participated of activities involving exposure dialogued, discussions with teachers/researchers and the application of questionnaires composing a set of data analyzed by mixed methods. The majority of students considered satisfactory the approach experienced in basic education in relation to interdisciplinarity (84%), problem situations (63%) and environmental issues (60%). However, they considered relevant to address these aspects in Mathematics, indicating good opportunities for the adoption of educational practices with transversality and interdisciplinarity in the framework of the teacher initial education. Keywords: Interdisciplinarity. Mathematics education. Teacher Education. Environmental Education. Problem-situations.